2004
DOI: 10.1002/adsc.200404122
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Asymmetric Morita—Baylis—Hillman Reaction Catalyzed by Chiral Brønsted Acids

Abstract: This report describes the development of a chiral Brønsted acid-catalyzed asymmetric MoritaBaylis À Hillman (MBH) reaction of cyclohexenone with aldehydes. During the course of our studies on chiral Lewis acid-promoted MBH reactions, we discovered that chiral binaphthol-derived Brønsted acids serve as promoters of the asymmetric MBH reaction. We propose that the phosphonium enolate of cyclohexenone is stabilized via hydrogen-bonding with the binaphthol-derived Brønsted acid, creating a chiral nucleophile. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…The ability of this species to function as a chiral H-bond donor was discovered by McDougal and Schaus in the context of enantioselective Morita-Baylis-Hillman reactions (Scheme 18). [72] The observation that acidic additives such as phenols accelerate Morita-Baylis-Hillman reactions constitutes important precedent for this work. [73] Optimization of the binaphthol structure revealed that arene-substituted octahydro(BINOL) derivatives such as 16 afforded high enantioselectivity for reactions of a range of aldehyde partners with 2-cyclohexenone in the presence of triethylphosphine.…”
Section: Diols Biphenols and Hydroxy Acidsmentioning
confidence: 99%
“…The ability of this species to function as a chiral H-bond donor was discovered by McDougal and Schaus in the context of enantioselective Morita-Baylis-Hillman reactions (Scheme 18). [72] The observation that acidic additives such as phenols accelerate Morita-Baylis-Hillman reactions constitutes important precedent for this work. [73] Optimization of the binaphthol structure revealed that arene-substituted octahydro(BINOL) derivatives such as 16 afforded high enantioselectivity for reactions of a range of aldehyde partners with 2-cyclohexenone in the presence of triethylphosphine.…”
Section: Diols Biphenols and Hydroxy Acidsmentioning
confidence: 99%
“…[48,49] Saturation of the BINOL derivative and introduction of bulky substituents on the 3,3'-positions are essential for the excellent enantioselectivity. They proposed that the phosphonium enolate of cyclohexanone is stabilized via a hydrogen bond with the binaphtholderived Brønsted acid, creating a chiral nucleophile.…”
Section: Binol Derivativesmentioning
confidence: 99%
“…(R)-3,3Ј-Bis(benzhydryl)-octahydro-1,1Ј-binaphthol (11) was prepared by reaction of (R)-octahydro-1,1Ј-binaphthol [22] with benzhydryl chloride. [23] Phosphorylation of 11 (0.120 g, 0.19 mmol) was performed with POCl 3 (37 mL, 0.40 mmol) in pyridine (0.6 mL) over 1 h at 90°C.…”
Section: (R)-33ј-bis(benzhydryl)-octahydro-11ј-binaphthyl Phosphatementioning
confidence: 99%